Carbon-Isotopic Composition of Atmospheric CO2 since the Last Glacial Maximum - Wahlen, Martin (IEDA: US Antarctic Program Data Center, 2002)
Abstract: These data describe the concentration and carbon-isotopic composition (d13CO2) of atmospheric CO2 from air trapped in ice between 27,000 and 1,300 years before present from Taylor Dome, Antarctica. Data are used to investigate the causes of the CO2 concentration increase that occurred during the transition between the last glacial maximum (LGM) and the Holocene. Data are in tab-delimited ASCII and Excel formats, and are available via ftp.